The effect of green algae on the growth parameters of Linum usitatissimum tissue and on its secondary metabolites content - R. T. Yahya; H. M. Yaqub; S. N. Ghanim; A. A. H. Mohammed (Regulatory Mechanisms in Biosystems, 2025)
This study was undertaken to determine the effect o n the growth of flax ( Linum usitatissimum L.). of enriching the nutrient medium by an extracellular product of algae ( Cladophora glomerata , Chara sp.) The effect of application of algae to M ur a shige and Skoog medium on plant growth and pigment content contrasted favorably with the effect of the media without algae. We recorded the highest response in seedling growth, which registered 14.8 cm and 14.4 mg, for length and dry weight of shoot, respectively, 16.4 cm for root length and chlorophyll a total content at 0.5% , from Chara extract. Phenolic compounds quercetin, syringic acid, rutin, ferulic, vanillic aci d, p -coumaric and g allic acid were measured by high-performance liquid chr omatography (HPLC) analysis, the results indicated that the highest content of phenols was found in flax seedling tissues treat ed by Chara 0.5% compared to control (without algae).